Lipoxin A4 promotes autophagy and inhibits overactivation of macrophage inflammasome activity induced by Pg LPS. Issue 2 (February 2021) - Zhao, Jie; Geng, Wenjing; Wan, Kefei; Guo, Kailei; Xi, Fengjun; Xu, Xiangqun; Xiong, Xiujuan; Huang, Xu; Liu, Jiayi; Kuang, Xiaodong
Objective: To explore the role of lipoxin A4 (LXA4) on inflammasome and inflammatory activity in macrophages activated by Porphyromonas gingivalis lipopolysaccharide (PgLPS) one of the major causative agents of chronic periodontitis. Methods: The mouse macrophage cell line RAW264.7 was used to produce an activated inflammation model. Markers of inflammasome and inflammatory activity and autophagy were assessed by ELISA, reverse transcription polymerase chain reaction (RT-PCR), and Western blot assay. Results: Markers of inflammasome activity, inflammation and autophagy increased with Pg LPS concentration. They also increased with increasing exposure to Pg LPS up to 12h but decreased at 24h. However, markers of autophagy increased. Phosphorylated NF-κBp65 decreased with LXA4, which was similar to results obtained with the autophagy inducer, rapamycin. Conclusions: LXA4 promoted autophagy and inhibited activation of inflammasomes and inflammation markers in macrophage inflammation induced by PgLPS and this action was linked to the phosphorylation of NF-κB.